Unveiling the influence of ultrasonic-assisted lipolysis: A pilot study of short-chain fatty acid profiling in human milk based on mass spectrometry. (October 2022) - Li, Hong; Jia, Keyu; Wu, Meng; Chen, Ming
Highlights: Ultrasonic-assisted lipolysis was applied to sample pretreatment. Breaking HMFG membranes contributed to VA and HA concentrations. A complete HM SCFA profile including PA and VA was performed. LC-ESI-MS was applied to HM SCFA profile for the first time. Performance characteristics of GC-EI and LC-ESI in HM SCFA detection were assessed. Abstract: Short-chain fatty acids (SCFAs) were recently emerging components in human milk (HM), which might have positive effect on the growth and development of infants. Thus, rapid monitoring of SCFAs in HM, as well as their physiological roles, was vitally important. In this study, the complete profiling of HM SCFA was established in order to further understand the potential association of SCFA with human milk fat globule (HMFG) membranes. A new liquid-liquid extraction coupled with crucial pretreatment of ultrasonic-assisted lipolysis was used to break HMFG membranes efficiently, releasing valeric acid (VA) and hexanoic acid (HA) from their lipid-binding forms, while unchanged acetic acid (AA), propionic acid (PA) and butyric acid (BA). Moreover, an inter-platform comparison for the rapid semi-quantification of HM SCFAs, based on gas chromatography and liquid chromatography-mass spectrometry (GC–MS/LC-MS) was also performed. Our observations linked certain features of AA and HA, such as higher intensity under electron impact ionization than under electrospray ionization, to method performance characteristics. The concentrations of most SCFAs, obtained by GC-MS and LC-MS, showed consistent trends among individuals ( p <  0.0001). This study was the first report on the comparative analysis of HM SCFA profiling, with all detectable components including AA, PA, BA, VA, and HA.